Variation of the different attributes that support the physical function in community-dwelling older adults - Pereira, Catarina (2013)
AIM: This study investigated the variation with age of different attributes that support the physical functioning in community-dwelling older adults having as reference scores from young adults. METHODS: The study was a cross-sectional study. Participants were 559 older adults and 79 young adults grouped according to gender and age (Y:20-29, A:60-64, B:65-69, C:70-74, D:75-79 and E:≥80 years). Strength, flexibility, agility, aerobic endurance, and balance were evaluated by Fullerton tests. RESULTS: ANOVA and Bonferroni post-hoc tests showed that compared to young, the 60-64 years group showed decreased values in almost all attributes of physical function. In older adults, additional differences were observed in females mainly between the 60-64 years group and the 70-74 years, 75-79 years, and:≥80 years groups, and in males between the 60-64 years group and the ≥80 years group (P<0.05). Comparisons between standardized physical function attributes (T-scores) done by repeated measures and contrasts demonstrated that, across age groups, agility and dynamic balance showed the highest rate loss in both genders, and lower body flexibility showed the lowest (P<0.01). CONCLUSION: Physical function reduction seems to occur earlier in women than in men and abilities involving multiple structures such as balance, agility, and aerobic endurance showed the most loss.